The Impact of the Project Based Learning Model on the Critical Thinking Skills of Vocational High School Students - Taufiq (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to test the effect of the project-based learning model on the critical thinking skills of vocational high school students. This study is a quantitative study with an experimental research type. The experimental design used is a quasi-experiment involving 11th-grade students of SMK Negeri 1 Muarabatu who were divided into two groups, namely the experimental group and the control group. The data of this study are quantitative data collected using critical thinking ability test techniques. The collected data were then analyzed using descriptive statistical test techniques by testing the average value, standard deviation and percentage of completeness, as well as inferential statistical tests using independent t-tests and paired t-tests. The results of the study indicate that the influence of the project-based learning model has a positive and significant effect on the critical thinking skills of vocational high school students. This is evident from the research data which shows that the average value of students' critical thinking skills in the experimental class is higher (92.17) than the control class (76.63). In addition, the standard deviation value also shows that the standard deviation value of the experimental class is smaller than the control class, which means that students' critical thinking skills in the experimental class are more evenly distributed. Furthermore, the percentage of student completion showed that the experimental class achieved 90.61%, while the control class only achieved 73.33%. The results of the independent t-test and paired t-test showed that the significance value was smaller than the alpha value, which was 0.000 (<0.005). Based on these results, the influence of the project-based learning model can be used as an alternative to address the low critical thinking skills of vocational high school students.